2016
DOI: 10.1177/1741143216662923
|View full text |Cite
|
Sign up to set email alerts
|

What disability? I am a leader! Understanding leadership in HE from a disability perspective

Abstract: This article is based on the findings of an externally funded, mixed-methods research project conducted at one English university. This small-scale project aimed to examine leadership, barriers to becoming a leader and the support needed to overcome them, from the perspectives of disabled staff. An online questionnaire was sent to all 66 members of staff who had disclosed their disabled status to the university and 22 responses were received. Twelve participants were then interviewed as two focus groups to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…International literature also identifies significant gaps between policy and practice, as well as difficulty in maintaining accommodations once obtained (Stone et al, 2013; Williams and Mavin, 2015). In the university context, managers are key figures in providing workplace adjustments (Emira et al, 2018). Managers may determine what assistance is provided and what is considered reasonable (Corlett and Williams, 2011; Gregly, 2017 in Newton et al, 2018).…”
Section: Capitalism Disability and The Ideal University Workermentioning
confidence: 99%
“…International literature also identifies significant gaps between policy and practice, as well as difficulty in maintaining accommodations once obtained (Stone et al, 2013; Williams and Mavin, 2015). In the university context, managers are key figures in providing workplace adjustments (Emira et al, 2018). Managers may determine what assistance is provided and what is considered reasonable (Corlett and Williams, 2011; Gregly, 2017 in Newton et al, 2018).…”
Section: Capitalism Disability and The Ideal University Workermentioning
confidence: 99%
“…Acker, 1983), less is known about how the 'greedy institution' of academia's work demands affects those academics who are disabled or have chronic health conditions (Williams and Mavin, 2015). Disabled academics are less likely to be found in leadership positions (Emira et al, 2018) and, along with other marginalised groups, are less likely to be submitted for research assessment processes (Leathwood, 2017). Impairment effects act as a career boundary (Williams and Mavin, 2015), resulting in the risk of being 'othered' within the competitive cultural environment of academe (Merchant et al, 2020).…”
Section: Disabled Academicsmentioning
confidence: 99%
“…Although research has investigated leadership among neurodiverse individuals, the focus of these studies has primarily been on descriptive accounts of their leadership experiences. Research has drawn attention to neurodiversity characteristics as impediments to the development of the effective social relationships through which leadership occurs (Hurley-Hanson & Giannantonio, 2017), and highlighted an array of institutional and personal barriers that diminish the likelihood of neurodiverse individuals being perceived as leaders (see Emira, Brewster, Duncan, & Clifford, 2018). For example, the results of a study on leadership emergence among people with learning disabilities showed that having a disability negatively impacted both peer perceptions of leadership potential and leadership role occupancy, although no significant differences in leadership effectiveness were indicated in supervisor and peer evaluations (Luria, Kalish, & Weinstein, 2014).…”
Section: Can Neurodiverse Individuals Be Leaders?mentioning
confidence: 99%
“…These more task-focused approaches to leadership may provide conceptual space for neurodiversity. Although prior research has highlighted neurodiverse individuals’ social capabilities as barriers to being perceived, engaged, and supported as leaders (Emira et al, 2018), such exclusion may also be attributable to the current emphasis on the social properties of leadership. With an implicit assumption that leader effectiveness is driven by interpersonal behaviors, certain characteristics of neurodiverse individuals have been considered impediments to leadership.…”
Section: Can Neurodiverse Individuals Be Leaders?mentioning
confidence: 99%